Evaluasi Penerapan Standar Akuntansi Keuangan Pemerintah (SAK-IP) Dalam Pengelolaan Aset Tahun 2025 (Studi Kasus: Bidang Aset Kantor Badan Keuangan Daerah Kabupaten Kepahiang) - M. Reza Oktananda; Puspa Rini (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study aims to evaluate the implementation of Government Accounting Standards (SAK-IP) in the management of fixed assets within the Regional Financial Agency (BKD) of Kepahiang Regency. Using a descriptive qualitative approach, data were collected through in-depth interviews, direct observations, and document analysis. The research focuses on the procedures for asset accountability reporting, the level of compliance with SAK-IP, and the main challenges encountered in its implementation. The findings reveal that although asset reporting procedures have been formally established and supported by the SIMDA BMD system, several issues persist, including delays in data submission, incomplete asset documentation, and limited human resource capacity. The level of compliance with SAK-IP is categorized as moderate, with core principles such as historical cost-based asset recording being applied, while other aspects like depreciation and revaluation are inconsistently implemented. The primary obstacles identified include the lack of technical training, inadequate interdepartmental coordination, and insufficient budgetary support. This research recommends improving staff competency, enhancing inter-agency collaboration, and strengthening systems and regulations to ensure more accountable and accrual-based asset management.